83=-5x+3(-3x-5)

Simple and best practice solution for 83=-5x+3(-3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 83=-5x+3(-3x-5) equation:


Simplifying
83 = -5x + 3(-3x + -5)

Reorder the terms:
83 = -5x + 3(-5 + -3x)
83 = -5x + (-5 * 3 + -3x * 3)
83 = -5x + (-15 + -9x)

Reorder the terms:
83 = -15 + -5x + -9x

Combine like terms: -5x + -9x = -14x
83 = -15 + -14x

Solving
83 = -15 + -14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14x' to each side of the equation.
83 + 14x = -15 + -14x + 14x

Combine like terms: -14x + 14x = 0
83 + 14x = -15 + 0
83 + 14x = -15

Add '-83' to each side of the equation.
83 + -83 + 14x = -15 + -83

Combine like terms: 83 + -83 = 0
0 + 14x = -15 + -83
14x = -15 + -83

Combine like terms: -15 + -83 = -98
14x = -98

Divide each side by '14'.
x = -7

Simplifying
x = -7

See similar equations:

| (3/7)*p=48 | | 1.4h=1.8h+4.8-.4h | | 4+-22= | | (X+2)+(2x+2x)=4x+x | | 2(2-4n)=28 | | -50=2x-7(x+15) | | -25-5= | | x+3.4=6.9 | | -5x+4(3x-10)=-82 | | -3x-4=4+10 | | 6-5t=4+3t | | 10x^2+y^2=110 | | 3p+9-2p=11-7 | | [7*(8+8)]+9=y | | 36x^2-196x=0 | | k/4+2(3k-1)/3 | | x^5+3x-9=0 | | 4x+7x-58=107 | | 7.62*3.14= | | 23-2a=3(6a-4) | | x/4+4=7-z/4 | | 12x-109-6x=71 | | 44=3(-4n-7)-7(-7n-4) | | x-(x*.15)=150 | | 10/1.167 | | 6(h-2)=6 | | 4x+8=x+9 | | -83-9x-3x=193 | | 4y-36x=28 | | 0=2x^2+4xh-A | | 16b^2=36+36b | | -12x+x-71=127 |

Equations solver categories